Sintering and mechanical properties of MgO-doped HA bioceramic - Ramesh S.; Tolouei R.; Amiriyan M.; Tan C.Y.; Sopyan I.; Hamdi M.; Purbolaksono J.; Teng W.D. (2023)
In the present research, nano hydroxyapatite (HA) powder doped with magnesia (MgO) was studied. The dopant was added to pure HA powder and ball milling was done for 1 hour. Green samples, in the form of discs and rectangular bars, were prepared and consolidated in air at temperatures ranging from 1000 C to 1300 C. The sintered samples were characterized to determine the phase stability, relative density, hardness, fracture toughness and Young's modulus. The phase analysis revealed that the HA phase was not disrupted regardless of dopant additions and sintering temperature. It has been revealed that all HA samples achieved >98% relative density when sintered between 1100 C-1300 C. However, the addition of 0.5 wt% MgO when sintered at 1100 C was found to be most beneficial in aiding sintering with samples exhibiting the highest Young's modulus of 122.15 GPa and fracture toughness of 1.64 MPa m1/2 as compared to 116.57 GPa and 1.18 MPa m 1/2 for the undoped HA. 2012 American Scientific Publishers. All rights reserved.